Difficulties Of Grade X Students In Writing Descriptive Texts At SMA Negeri 3 Palu - Pelangi Putri Rahayu; Mawardin M. Said; Budi Budi; Mukrim Mukrim (Hasanuddin University, 2026)
This study aims to identify and describe the specific difficulties experienced by Grade X students at SMA Negeri 3 Palu in writing descriptive texts in English. More specifically, the study seeks to examine students’ understanding of the generic structure of descriptive texts, their use of vocabulary, and their application of grammatical rules in writing. A qualitative descriptive research design was employed to provide a detailed picture of students’ writing problems based on their own responses. Data were collected through an online questionnaire distributed to Grade X students who had learned descriptive text writing in their English classes. The findings reveal that students face several challenges when writing descriptive texts. Many students had difficulty distinguishing between the identification and description parts of the text, which often resulted in unclear or incomplete descriptions. Students also reported limited vocabulary, making it difficult for them to express ideas clearly and vary their word choices. In addition, grammatical problems, particularly in the use of tenses and sentence structure, were frequently identified as major obstacles in their writing. These results are consistent with previous studies that report similar difficulties among EFL learners in writing descriptive texts. Limited mastery of vocabulary, grammar, and text organization has been widely recognized as a key factor affecting students’ writing performance. The findings suggest that students need more structured guidance and practice to develop these skills. Therefore, this study recommends that English teachers provide focused instruction and targeted training to help students better understand text structure, expand their vocabulary, and improve grammatical accuracy in descriptive writing.